ASSESSMENT OF GENETIC DIVERSITY BY RANDOM AMPLIFIED POLYMORPHIC DNA (RAPD) AND ATPASE 6/8 GENE IN Pangasiuspangasius - Shoaib hassan; Muhammad Naeem (Journal of Animal and Plant Sciences, 2023)
The aim of the present study was to use RAPD and ATPase markers to measure and analyze the level of genetic variation within farm cultured populations of introduced Pangas catfish Pangasius pangasiusto evaluate their potential in ascertaining genetic differentiation. Hence, genetic diversity of farmed P.pangasius was carried out from five different sites by using RAPD primer. Primers showed 151 total amplified locus with an average of 37.75 loci. The highest number of bands were observed in P.pangasius from population 1, maximum no of bands was observed in OPA-02 (56 bands), while the minimum from OPA-05 (26 bands). Minimum polymorphism was observed in OPA-08 (10.71%), while maximum in OPA-01 (66.67%). The value of heterozygosity of P. pangasius ranged from 0.123 to 0.444.A cluster between population 1 and 2, 2nd population 3 and 4, and population 5 with all other as 3rd cluster. Distance found maximum in population 5 that showed heterozygosity. The genetic variations and polymorphism among populations showed the degree of intra and inter-population genetic diversity in P. pangasius populations. Study is also done to access the genetic diversity by ATPase 6/8 gene. ATPase 6/8 showed highest haplotype diversity (0.800) in the P. pangasius population of Tariq Khan Faheem Fish Farm, while the lowest (0.700) in Al-Raheem fish Farm. Highest nucleotide diversity (0.703) in Tariq Khan Faheem Fish Farm, while lowest (0.5026) in Mirza Rizwan Ahmed Fish farm. Higher diversity is important for conservation and management of population.Random amplified polymorphic DNA (RAPD) and ATPase 6/8 markers were used to estimate the genetic diversity and population structure among the samples of farmed P. pangasius. Overall, RAPD and ATPase 6/8 proved as valuable tool for reliable and quick stock discrimination and provided information that might be useful regarding management and conservation of P. pangasius. The findings will be helpful in developing stock specific management measures for conservation and sustainable utilization of the species.
Keywords: Genetic diversity; ATPase 8/6; RAPD; Fish; P. pangasius